Deviations in the Community (Law Research Review Quarterly, 2020)
Karaoke and the Bar in many cases serve as a place of illegal prostitution. This right is a deviation in society. The purpose of this study is to find out how karaoke guides do the work in Bandungan and the background of these actions. This research is a qualitative research with a descriptive approach. The subjects consisted of seven karaoke guides and one boarding house owner. In data collection techniques using observation, interviews, and documentation. Data analysis uses conclusion drawing. The results of this study, karaoke guides in Bandungan Kabuaten Semarang were formed due to economic base, low education and environmental factors. In addition to serving as a karaoke guide, this karaoke guide woman can be hired for dating and concurrently a profession as a Commercial Sex Workers or CSWs. Customers and song guide women do transactions outside the karaoke place. There is agreement between the two before engaging in covert prostitution practices.